2017
DOI: 10.1111/ele.12802
|View full text |Cite
|
Sign up to set email alerts
|

Feedbacks between plant N demand and rhizosphere priming depend on type of mycorrhizal association

Abstract: Ecosystem carbon (C) balance is hypothesised to be sensitive to the mycorrhizal strategies that plants use to acquire nutrients. To test this idea, we coupled an optimality-based plant nitrogen (N) acquisition model with a microbe-focused soil organic matter (SOM) model. The model accurately predicted rhizosphere processes and C-N dynamics across a gradient of stands varying in their relative abundance of arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) trees. When mycorrhizal dominance was switched - ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 45 publications
3
138
0
Order By: Relevance
“…Recent work incorporating N cycling into the CORPSE model (Sulman et al, 2017) will allow us to investigate the role of N limitation on subsoil SOC decomposition in future analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work incorporating N cycling into the CORPSE model (Sulman et al, 2017) will allow us to investigate the role of N limitation on subsoil SOC decomposition in future analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We simulated decomposition of isotope-labeled root litter by initializing the model with 0.5 mg of root mass, which was assumed to contain 25% rapidly-decomposing compounds and 75% slowly-decomposing compounds in line with previous CORPSE simulations (e.g., Sulman et al, 2017). We drove the model for the 15, 55, and 95 cm depths by interpolating measured profiles of soil temperature and moisture to the appropriate depths.…”
Section: Download High-res Image (846kb)mentioning
confidence: 99%
“…The apparent rate of carbon accumulation in the peat layers above the mean water‐table depth approximated c. 90 g C m −2 year −1 for the low elevation site and c. 154 g C m −2 year −1 for the high elevation site over a reference period of 26–30 years for both sites, a result suggesting a lower carbon sink capacity of peatlands at the lower end of their altitudinal distribution (Millar, Cooper, Dwire, Hubbard, & von Fischer, ). The effective annual contribution of the rhizosphere priming to the observed difference in carbon accumulation rate in relation to the dominant vascular plant functional types and their symbiotic microorganisms remains an open question that deserves further attention (Gavazov et al., ; Sulman et al., ; Walker et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal types strongly affect soil C cycling via differences in litter decomposition and priming. Based on ecosystem models of enzymatic activities of excised root tips, Sulman et al (2017) suggested that in newly established vegetation, EcM systems retain soil C of previous AM-dominated habitats, but AM vegetation slowly releases soil C originating from previous EcM-dominated forest. These models contradict the earlier suggestions that EcM fungi deplete accumulated soil C in exotic forestry plantations (Chapela et al, 2001), indicating some context dependency or differences in accounting for active and passive losses.…”
Section: (3) Soil Carbon Cyclingmentioning
confidence: 99%